EFL Students' Psychological Well-Being in Learning across Different Epistemic Beliefs Levels - Tyara Muffidah Listyadi; Ive Emaliana; Alies Poetri Lintangsari; Irene Nany Kusumawardani (Indonesian Journal of EFL and Linguistics, 2023)
Epistemic beliefs of English language learning (EFL) learners are one of the factors that have increased awareness among people due to their pivotal role in influencing students' success and learning strategies and behaviors. The current study aims to compare the two variables above and thus investigate EFL university students' psychological well-being across different levels of Epistemic Beliefs. This quantitative study uses an independent sample T-test to determine the mean difference between two independent groups, which are the psychological well-being (henceforth, PWB) and epistemic beliefs of EFL students. The data was gathered by delivering online questionnaires via Google Forms to 96 students from a reputable university in East Java, Indonesia, majoring in English language education. The results indicate that there is no difference in the psychological and emotional well-being of students in the study area among different levels of epistemic beliefs (i.e., sophisticated and simple). According to the findings, investigating students' epistemic beliefs can provide insights into their educational engagement and well-being when studying. It is found that the PWB of different epistemic beliefs of Indonesian EFL learners is not that significant, and it is implied that epistemic beliefs are a spectrum that can be influenced by other aspects, such as cultural facets.